2023
DOI: 10.3934/neuroscience.2023017
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of dopamine in Parkinson's disease and relevant therapeutic options: A review of the literature

Abstract: <abstract> <p>Parkinson's disease (PD) is a progressive neurodegenerative disorder that affects motor and cognition functions. The etiology of Parkinson's disease remains largely unknown, but genetic and environmental factors are believed to play a role. The neurotransmitter dopamine is implicated in regulating movement, motivation, memory, and other physiological processes. In individuals with Parkinson's disease, the loss of dopaminergic neurons leads to a reduction in dopamine levels, which caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The degeneration of dopamine-producing neurons in the SN and OB is a prominent neuropathogenic hallmark of PD [40,41]. As a consequence, reduced levels of dopamine in the brain have been directly linked to motor deficits, olfactory dysfunction, and memory loss in PD [42]. Interestingly, S. Szabo and C.H.…”
Section: Discussionmentioning
confidence: 99%
“…The degeneration of dopamine-producing neurons in the SN and OB is a prominent neuropathogenic hallmark of PD [40,41]. As a consequence, reduced levels of dopamine in the brain have been directly linked to motor deficits, olfactory dysfunction, and memory loss in PD [42]. Interestingly, S. Szabo and C.H.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease is a neurodegenerative disorder characterized by the loss of dopamineproducing neurons in the substantia nigra, a region of the brain involved in movement control [110]. This loss of dopamine leads to the motor symptoms of Parkinson's disease, including bradykinesia (slowness of movement), rigidity, tremor, and postural instability.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Modulations in neurotransmitter distribution and receptor sensitivity may contribute to differences in PD motor symptoms between men and women. For example, dopamine is a neurotransmitter involved in the regulation of movement, and its deficiency is related to the motor symptoms of PD; changes in the function of dopaminergic receptors affect the transmission of nerve signals and the consequent manifestation of motor symptoms ( Ramesh and Arachchige, 2023 ). Many studies have reported that in women, motor symptoms tend to emerge later and are characterized by reduced rigidity, tremor, and a greater propensity to develop postural instability ( Cerri et al, 2019 ).…”
Section: Gender Differences In Pd Symptoms and Progressionmentioning
confidence: 99%